The Influence Of Tenure, Job Satisfaction And Organizational Culture On Organizational Citizenship Behavior At Hospital - Soesianingsih , Njoman Oly; Chalidyanto, Djazuly; Damayanti, Nyoman Anita; Budhi Setianto (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
Organizational Citizenship Behavior (OCB) is a voluntary act of creativity and innovation designed to enhance an individual's or organization's performance with persistence and enthusiasm, involving taking more responsibility and encouraging others to do the same. One of the challenges that must be faced is low OCB. Instances reflecting low OCB behavior include difficulty finding replacements when colleagues are not available, a lack of commitment to tasks beyond routine work, and a strong sense of indifference. Therefore, an analysis is needed to determine the relationship between tenure, job satisfaction, organizational culture, and OCB at Delta Surya Sidoarjo Hospital. The research method used is descriptive quantitative. The number of randomly selected respondents was 165. There were two variables in this study: the independent variable and the dependent variable. Independent variables include tenure (X1), job satisfaction (X2), and organizational culture (X3). The dependent variable in this study was Organizational Citizenship Behavior (Y). Two data analysis techniques employed in this study: the linear regression test and the chi-square test. Based on the research results, it was found that the measurements of Organizational Citizenship Behavior for Delta Surya Hospital employees on December 19, 2022, showed that 33.33% of employees had high OCB, while 66.66% had low OCB. Using the linear regression test, it was stated that tenure did not affect OCB (sig = 0.396), Organizational Culture affected OCB (sig = 0.000), and job satisfaction influenced OCB (sig = 0.000). Job satisfaction at Delta Surya Hospital is high, while Organizational Culture and Organizational Citizenship Behavior are low. Job Satisfaction and Organizational Culture affect Organizational Citizenship Behavior, while tenure has no effect.